Factors associated with receipt of crosslinking for Keratoconus - Son, Hyeck Soo; Nugent, Liam; Wang, Jiangxia; Varadaraj, Varshini; Smith, Kerry; Bower, Kraig S.; Mgboji, Glory; Soiberman, Uri S.; Srikumaran, Divya (Cornea, 2024)
Purpose: - The aim of this study was to identify factors associated with receipt of standard fluence epithelium-off crosslinking (CXL) for keratoconus (KCN). - Methods: - This retrospective, cross-sectional study reviewed electronic health records of treatment-naive patients with KCN seen at the Wilmer Eye Institute between January 2017 and September 2020. Tomographic data were derived from Pentacam (Oculus, Wetzlar, Germany) devices. Multivariable population-average model using generalized estimating equations adjusting for age, sex, race, national area deprivation index, vision correction method, and disease severity was used to identify factors associated with receipt of CXL. - Results: - From 583 patients with KCN, 97 (16.6%) underwent CXL for KCN. Patients who received CXL in at least 1 eye were significantly younger (mean 24.0 ± 7.8 years) than patients who had never undergone CXL (33.4 ± 9.3 years) (P < 0.001). In multivariable analysis, Black patients had 63% lower odds of receiving CXL for KCN (OR: 0.37, 95% CI, 0.18-0.79) versus White patients, and older age was protective against receipt of CXL (OR: 0.89 per 1-year increase, 95% CI, 0.86-0.93). Comparison of characteristics by race demonstrated that Black patients presented with significantly worse vision, higher keratometric indices (K1, K2, and Kmax), and thinner corneal pachymetry at baseline versus White or Asian patients. - Conclusions: - In this clinical cohort of patients with KCN from a tertiary referral center, Black patients were less likely to receive CXL presumably because of more advanced disease at presentation. Earlier active population screening may be indicated to identify and treat these patients before they become ineligible for treatment and develop irreversible vision loss. Such strategies may improve health equity in KCN management.
Gesehen am 13.03.2024